Efficiency performance analysis of series loaded resonant converter - McCarty, Michael (IEEE, 2009)

(untitled)
Series Loaded Resonant (SLR) converter is a well known topology typically used in kilowatt-range power supplies. The topology may operate in either continuous or discontinuous conduction modes whose switching properties are covered in many power electronic text books. However, information related to the actual converter's efficiency for each conduction mode is lacking and thus will be addressed in this paper. The development of a lab scale SLR converter will be described along with results of computer simulation. Efficiency performance from hardware results for each conduction mode when output power and switching frequency are varied will also be discussed.